Effect of Qnr on Plasmid Gyrase Toxins CcdB and ParE - Kwak, Yee Gyung (Antimicrob Agents Chemother, 2015)
Plasmid toxins CcdB and ParE are part of addiction systems promoting plasmid maintenance. Both target host DNA gyrase, as do quinolones and plasmid-determined Qnr proteins that protect gyrase from quinolone inhibition. We cloned qnrB4, qnrS1, ccdB, parE, and the antitoxin-encoding genes ccdA and parD on compatible plasmids and tested them in combination. CcdB and ParE had no specific effect on quinolone susceptibility or Qnr protection, and Qnr did not act as a CcdB or ParE antitoxin.